Si3N4 reinforced Al-Si-Mg matrix composites: Powder metallurgy fabrication, PEO coating and characterization - Yurekturk, Yakup; Senyurt, Berk; Celtik, Cansu; Kucukelyas, Burak; Akcamli, Nazli (Elsevier, 2025)
Si3N4-reinforced Al-6.5Si-0.5Mg matrix composites were produced via a powder metallurgy (PM) method, which includes high-energy mechanical milling (HEBM) and pressureless sintering. An oxide-based ceramic protective coating was applied to the PM composites using the plasma electrolytic oxidation (PEO) technique. The novel aspect of this study lies in applying a PEO coating on particulate-reinforced AMCs produced through PM, which further enhances the composites' surface properties and corrosion resistance. The microstructural characterizations indicate that the mechanically alloyed (MA'ed) powders comprise Si and Mg phases integrated within the Al matrix along with embedded Si3N4 reinforcement particles, thus ensuring a composite structure. Hence, applying the mechanical alloying (MA) process and Si3N4 incorporation enhanced the densification and hardness properties of the Al-Si-Mg matrix, highlighting its reinforcing effect. The hardness of MA'ed and 15 wt% Si3N4incorporated composite increases to 144 HV. Also, the PEO-coated samples outperform all uncoated samples in terms of corrosion resistance. The PEO-coated Al-6.5Si-0.5Mg-15Si3N4 composite showed an approximate 89% decrease in corrosion rate compared to the uncoated Al-6.5Si-0.5Mg base alloy. Thus, the PEO-coated sample with 15 wt% Si3N4, demonstrates superior performance, with the highest polarization resistance and a balanced charge transfer resistance, making it the most effective in corrosion protection.
Keywords: Aluminum-Matrix Composites; Silicon Nitride; Powder Metallurgy; Plasma Electrolytic Oxidation; Structure; Corrosion Properties